Testimonianza. Diario collettivo ai tempi della pandemia: Griseldaonline, 3-15 aprile 2020 - Elisabetta Menetti (Laboratoire Italien)
This essay looks at the Diario da una quarantena published in Griseldaonline between 3 and 15 April 2020 and addresses some issues relating to distance learning in schools and universities during Italy’s first Covid-19 lockdown.